Visual communication and user experience design in shaping the digital museum environment: Theoretical and practical aspects - Azzaari, Ali (Art and Design, 2026)
The relevance of this study is conditioned by the need to develop new approaches to designing digital museum spaces that would combine humanitarian and technological knowledge, meet contemporary audience needs, and contribute to the development of an inclusive, accessible, and culturally rich experience. The purpose of the study was to comprehensively analyse the role of visual communication and user experience design in the development of a contemporary digital museum space, and to identify the main concepts, principles, and approaches to creating an effective museum experience in a digital environment. To achieve this goal, the author used structural and functional, comparative, historical methods, and methods of design analysis, semiotics of visual images, principles of architectonics of user experience design and interface usability. The basic principles of interface organisation were defined, contemporary approaches to creating interactive and inclusive user experience were analysed, and the practical significance of implementing innovative design solutions in the museum sphere was outlined. It was determined that the digital museum environment is formed at the intersection of cultural studies, art history, information technologies, and design communications. Successful examples of digital museums and online archives where user experience design and user interface design transform the way cultural heritage was perceived were analysed. Based on an analysis of successful examples of digital museums (Google Arts & Culture, British Museum, Museum of Modern Art) user experience design and user interface design have been found to have a significant impact on the accessibility, personalisation, and emotional perception of cultural content. Theoretical and methodological approaches to the interaction of user experience design and visual communication in the museum environment were formulated, identifying new formats of interface visualisation that can activate interest in a cultural product in the digital sphere. The research can be used by specialists in the field of museum business, graphic design, interface development, and digital humanities to create innovative exhibition practices